A case of pylephlebitis complicating an acute appendicitis: Uncommon cholangitis-like situation. (October 2022) - Dalmau, Mar; Petrola, Carlos; Lopez, Pablo; Vilallonga, Ramon; Garcia Ruiz de Gordejuela, Amador; Armengol, Manel
Abstract: Introduction: Pylephlebitis represents an uncommon but serious condition with significant mortality which can complicate intrabdominal sepsis of any etiology. One of the most common predisposing infections is appendicitis. Presentation of case: A 21-year-old male with 4 days of epigastric and right upper quadrant pain with associated fever and chills with hyperbilirubinemia and leukocytosis in blood test was orientated as cholangitis at first diagnostic. Poor response to antibiotic treatment with persistent fever and bacteriemia with E. coli and S. constellatus isolated in blood cultures led to complete the study with a CT scan which revealed an acute appendicitis complicated with thrombosis of the superior mesenteric vein (SMV) up to the splenoportal confluence. Appendectomy, treatment with broad-spectrum antibiotic and anticoagulation treatment led to full recovery. Follow-up after 6 months showed almost complete SMV patency. Discussion: Pylephlebitis can present as a clinical cholangitis-like picture with hyperbilirubinemia with or without liver abscess formation. CT scan seems to be the most sensitive diagnostic test as it identifies the underlying focus of infection, the extension of the thrombosis and detects liver abscesses. Surgical removal of the source of infection as appendectomy and adequate antibiotic treatment adjusted by culture should be initiated promptly. Anticoagulant treatment should be considered in the case of poor clinical outcome or thrombosis progression. Conclusion: Pylephlebitis should be suspected mainly in patients with appendicitis and diverticulitis with erratic behavior despite surgical removal and/or antibiotic treatment with abnormal liver tests and persistent bacteriemia. CT scan is the preferred image study. Highlights: Pylephlebitis represents an uncommon but serious condition. Main cause has to be extensively investigated. Appendicitis is a potential cause of pylephlebitis. Pylephlebitis should be suspected mainly in patients with appendicitis and diverticulitis with erratic behavior.